(untitled) (Journal of Medical & Health Sciences Review, 2025)
Buckwheat relates to the family of crops Polygonaceae which has the property of free of gluten. It is rich in health-promoting phytonutrients because of its high nutritional content and potential to improve health, buckwheat is being included in diets as a substitute crop. The Flour of Buckwheat helps with hypercholesterolemia, obesity, hypertension, and diabetes according to studies conducted on animal models. The grains and other tissues of buckwheat contain many nutraceutical substances. These are abundant in dietary fiber, antioxidants, proteins, carbohydrates, and trace elements. Buckwheat comprises different types of bioactive compounds like vitamins, minerals, proteins, polysaccharides, fatty acids, flavonoids (such as rutin), and dietary fiber. Because of these bioactive components, buckwheat has a high nutritional value. Numerous gluten-free buckwheat products (BGFPs) have been produced, such as beer, pasta, breads, noodles, and pastries. This review aims to explore the current knowledge about buckwheat, its nutritional constituents, and the impact of Buckwheat on the characteristics of products and its potent application of diabetic-free products and buckwheat flour with high nutritional value for preparing free gluten chapatti with high nutritional value to overcome the health-related diseases as well as to target celiac illness people about (1.4% of the world population)